Studying bilinguals - Grosjean, Francois (Oxford University, 2008)
Includes bibliographical references (p. [291]-307) and index; Partial contents: Part V. Biculturalism, bilingualism, and deafness. The bicultural person: a short introduction -- The bilingualism and biculturalism of the deaf